Coherence effects and spin polarisation of electrons in electromagnetic fields - Quin, Michael (2023)
The collision of relativistic electrons with a counter propagating laser pulse can potentially generate short pulses of harmonics in the X-ray range, capable of tracking molecular, atomic and sub-atomic dynamics. Also, the creation of relativistic spin polarised electron beams is essential for probing spin dependent, fundamental interactions in particle physics. Our aim is to create a numerical code capable of modelling electron spin precession, while also predicting the spectrum and angular distribution of energy emitted from an arbitrary number of relativistic electrons, interacting with an external field in the domain of classical electrodynamics. This code will be rigorously tested against analytic solutions. With both numerical and analytic results, we can explore the conditions on the electron distribution necessary for generating coherent X-rays, and spin polarised electron beams. (Erratum: the fourth order Runge-Kutta integrator (RK4) as implemented in equations (2.9)--(2.11d) is actually a hybrid of the RK4 and second-order Leapfrog schemes; this estimates the position at the quarter and half steps using a leapfrog-type scheme. Strictly speaking, this is not a pure RK4 algorithm, as described. In practice, the time step was sufficiently small to ensure this did not affect any numerical results which were presented. The same comments apply to the integrator described in equations (2.23a)—(2.23d))
Keywords: Hochschulschrift